2021
DOI: 10.3389/fpsyg.2021.668139
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Word-, Sentence-, and Discourse-Level Abilities on Writing Performance: A 3-Year Longitudinal Study

Abstract: Writing is a foundational skill throughout school grades. This study analyzed the development of different levels of written language (word, sentence, and discourse) and explored the relationship between these levels and writing performance. About 95 Portuguese students from two cohorts—Grades 4–7 (n = 47) 6–9 (n = 48)—were asked to produce a descriptive text two times, with a 3-year interval. The produced texts were used to assess spelling, syntactic correctness and complexity, and descriptive discourse as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…One way to achieve this is to move away from the traditional binary correct vs. incorrect scoring method. Research has suggested that looking at children's misspellings beyond the dichotomous scoring system might reveal patterns of development in linguistic knowledge (Masterson and Apel, 2010;de Bree and van den Boer, 2019;Treiman et al, 2019; for non-English orthographies see also Niolaki and Masterson, 2012;Carvalhais et al, 2020Carvalhais et al, , 2021 and underlying cognitive processes that children use when they spell (Caravolas et al, 2001;Kessler, 2009;Treiman et al, 2016). These processes involve perception, attention, memory and expertise, all of which past research has explored in considerable depth (Georgiou et al, 2012;Rønneberg and Torrance, 2019;Zoccolotti et al, 2020;Niolaki et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One way to achieve this is to move away from the traditional binary correct vs. incorrect scoring method. Research has suggested that looking at children's misspellings beyond the dichotomous scoring system might reveal patterns of development in linguistic knowledge (Masterson and Apel, 2010;de Bree and van den Boer, 2019;Treiman et al, 2019; for non-English orthographies see also Niolaki and Masterson, 2012;Carvalhais et al, 2020Carvalhais et al, , 2021 and underlying cognitive processes that children use when they spell (Caravolas et al, 2001;Kessler, 2009;Treiman et al, 2016). These processes involve perception, attention, memory and expertise, all of which past research has explored in considerable depth (Georgiou et al, 2012;Rønneberg and Torrance, 2019;Zoccolotti et al, 2020;Niolaki et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The non-binary measures rely, for example, on how close the misspelled word is to the correct spelling and can be used as a fine-grained measure to monitor the progress a child is making in developing spelling skills (Masterson and Apel, 2010). Many children, especially in the Foundation Year, produce more errors than correct responses (Georgiou et al, 2020;Carvalhais et al, 2021), and the measures can provide us with a clear picture of the use of lexicalsemantic and sublexical processes, and how children's reliance on these processes changes as they progress in spelling skill. Also, error analysis is not affected by floor effects which is an issue when we solely look at accuracy especially for young spellers (Treiman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discourse can be defined as text or spoken language beyond the sentence level (Hughes et al, 1997;Nicolosi et al, 2004), while narratives are a genre of discourse also known as stories (Berman and Nir-Sagiv, 2007;Graham et al, 2013;Dockrell et al, 2014). Knowledge and use of narrative discourse requires a child to produce stories that contain specific structural features of narrative language and serves a specific communicative goal (Berman and Nir-Sagiv, 2007;Carvalhais et al, 2021). Narrative discourse is valued in the study of school-aged children's language because the ability to successfully produce a narrative is considered an important developmental milestone and is included in the Common Core State Standards for students in the United States (National Governors Association Center for Best Practices and Council of Chief State School Officers, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Peng et al (2019) showed that word reading developmental trajectories did not close until a hypothesized performance plateau was reached in the U.S. In a more recent study, Carvalhais et al (2021) traced the developmental paths at word, sentence, and discourse levels in Portugal. Lower results corresponded to lower academic years between grades 4 and 7 as well as 6 and 9.…”
Section: Introductionmentioning
confidence: 99%